Visión periférica en el tiempo de reacción en niños. - Cordero Espin, Kevin Roque (2024)
The present research focuses on the analysis of the reaction time of peripheral vision in boys and girls between eight and ten years of age from the Guano Cantonal Soccer School, located in the province of Chimborazo. For this, tests and posttests of peripheral vision and reaction time were applied. Among the tools used are Galton's cane and peripheral vision, in order to obtain information about the current state of the sense of sight and its possible deficiencies. The participating boys and girls were evaluated through ophthalmological examinations to detect eye diseases. With the results obtained from the eye exams, we proceed to train on the Cantonal League fields, executing various exercises with tracking techniques, repetitions, and specific activities, such as catch or chase games in which the child has to pay attention. of that happens around them on the playing field, during a period of one hundred and twenty days with two hours of training a day, looking to enhance peripheral vision and reaction time. Additionally, psychological and socioeconomic factors that could influence the research results were evaluated. The results obtained on the playing field are a significant contribution to the soccer team, as the players become more efficient in making passes and receiving them, thanks to optimal peripheral vision. The methodology used combines qualitative and quantitative aspects, with measurements that allow us to know the progress achieved through regular and specific practice. In summary, peripheral vision is a fundamental skill for success in games and sports, and can be trained and improved through specific activities and constant practice.